Agrobacterium tumefaciens mediated transformation of the aquatic carnivorous plant Utricularia gibba - Oropeza-Aburto, A. (Plant Methods, 2020)
BACKGROUND: The genus Utricularia belongs to Lentibulariaceae, the largest family of carnivorous plants, which includes terrestrial, epiphytic and aquatic species. The development of specialized structures that evolved for carnivory is a feature of this genus that has been of great interest to biologists since Darwin‘s early studies. Utricularia gibba is itself an aquatic plant with sophisticated bladder traps having one of the most complex suction mechanisms for trapping prey. However, the molecular characterization of the mechanisms that regulate trap development and the biophysical processes involved in prey trapping are still largely unknown due to the lack of a simple and reproducible gene transfer system. RESULTS: Here, we report the establishment of a simple, fast and reproducible protocol for genetic transformation of U. gibba based on the T-DNA of Agrobacterium tumefaciens. An in vitro selection system using Phosphinotricin as a selective agent was established for U. gibba. Plant transformation was confirmed by histochemical GUS assays and PCR and qRT-PCR analyses. We report on the expression pattern of the 35S promoter and of the promoter of a trap-specific ribonuclease gene in transgenic U. gibba plants. CONCLUSIONS: The genetic transformation protocol reported here is an effective method for studying developmental biology and functional genomics of this genus of carnivorous plants and advances the utility of U. gibba as a model system to study developmental processes involved in trap formation.